2014
DOI: 10.1016/j.psychres.2014.07.085
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine usage is associated with elevated processing speed, spatial working memory, and visual learning performance in youth at ultrahigh-risk for psychosis

Abstract: Research has stressed a link between nicotine and cognition in schizophrenia but this has not been examined in youth at ultra high-risk (UHR) for psychosis. A total of 35 UHR and 32 control participants were assessed for naturalistic nicotine-use and administered a cognitive battery. Smoking was reported more frequently in the UHR group (46%) than controls (22%). Frequent smoking was associated with elevated cognitive performance in the UHR group, highlighting a need for experimental investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…Nicotine and nicotinic agonists have been shown to significantly improve attention (Allison and Shoaib 2012), fear memory (Tian et al 2010;Lima et al 2013), and working memory (Levin and Simon 1998). Although nicotinic systems have been shown in numerous studies to be important for spatial working memory (SWM) in animals (Levin et al 2005;Fisher et al 2011;Mizoguchi et al 2011) and humans (Smith et al 2002;Sacco et al 2005;Wing et al 2011;Gupta and Mittal 2014), the brain regions and the mechanisms involved in nicotine-induced SWM alteration are less well known.…”
mentioning
confidence: 99%
“…Nicotine and nicotinic agonists have been shown to significantly improve attention (Allison and Shoaib 2012), fear memory (Tian et al 2010;Lima et al 2013), and working memory (Levin and Simon 1998). Although nicotinic systems have been shown in numerous studies to be important for spatial working memory (SWM) in animals (Levin et al 2005;Fisher et al 2011;Mizoguchi et al 2011) and humans (Smith et al 2002;Sacco et al 2005;Wing et al 2011;Gupta and Mittal 2014), the brain regions and the mechanisms involved in nicotine-induced SWM alteration are less well known.…”
mentioning
confidence: 99%
“…In the study conducted by Cadenhead, prevalence of current smokers was found to be 18% in at-risk individuals (N=89) and 32% in early psychosis patients (N=75) (converted to psychosis-and therefore no longer prodromal within the past 2 years) versus 14.1% in the control nonpsychiatric group (N=85) 53. Another estimate is provided by Gupta and Mittal,54 in a smaller sample, where UHR patients (N=35) reported nicotine use at a rate of 46% versus the 22% of the control group (N=32, P ≤0.05) 54. In the study of Buchy et al, the rate of tobacco use in a sample of Clinical High Risk (CHR) individuals (N=170) was 33.3%, with 2.8% corresponding to dependence or abuse 55.…”
Section: Resultsmentioning
confidence: 96%
“…Risk did not decline as the time to schizophrenia onset increased, suggesting that the association is not substantially attributed to the presence of a prodrome.Cadenhead (2011)53Case control, longitudinal studyThe Cognitive Assessment and Risk Evaluation (CARE) program, University of California San Diego249 [75 Early Psychosis (76.0% males), 89 At Risk for psychosis patients (60.7% males) and 85 nonpsychiatric control subjects (45.9% males)]DSM-IV or the Schedule for Affective Disorders and Schizophrenia for School-Age ChildrenStructured Interview for Prodromal Symptoms (SIPS)Development of psychosis per the SCID/KSADS criteriaClinical Interview. Dichotomous variable for current tobacco use: Yes/NoANOVA was repeated with tobacco and cannabis use as between subjects factors; subjects with current substance misuse excludedReduced Prepulse Inhibition (PPI) in early psychosis patients who smoke compared to nonsmokers; increased PPI in at risk subjects who smoke compared to nonsmokersGupta and Mittal (2014)54Cross-sectional, case control studyAdolescent Development and Preventive Treatment (ADAPT) program67 [35 Ultra High Risk (UHR) (63% males) and 32 Healthy Control, (HC) subjects (41% males)DSM-IVAttenuated Positive Symptom (APS) or Genetic Risk and Deterioration (GRD) prodromal syndromesNot applicableAlcohol/Drug Use Scale (AUS/DUS)Substance dependence disorder was exclusion criterionUHR subjects smoked more frequently than HC subjects, 46% vs 22%; Elevated cognitive performance in UHR smokers vs UHR nonsmokersZhang et al (2012)51Cross-sectional case control studyInpatients in the Beijing Hui-Long-Guan Psychiatric Hospital1336 (776 male patients with schizophrenia, 560 male healthy controls)DSM-IVNot specifiedNot specified- presumably conferred by the recorded illness course durationPatient,Questionnaire,Fagerstrom Test for Nicotine Dependence (FTND)Participants reported no dependence on any substance other than tobaccoMean age of smoking initiation 7 years (SD=10.2) before psychosis onset, during the early prodromal or premorbid period. Positive correlation between age at starting smoking and age at onset of illness ( P =0.005)Buchy et al (2014)55Longitudinal study/cross-sectional as for the substance use measuresMulti-site NIMH study “Enhancing the Prospective Prediction of Psychosis”(PREDICT),170 (96 men, 74 women) at Clinical High Risk (CHR) of psychosisNot applicable…”
Section: Resultsmentioning
confidence: 99%
“…They recorded significant improvements in information processing [22]. Several studies have shown that nicotine use may help to improve cognitive deficits in the population of schizophrenia patients [23,24], especially because as much as 72-90% of this population smoke cigarettes [25].…”
Section: Discussionmentioning
confidence: 99%